Shared spectrum access for the DoD. - Chan, Serena (IEEE Communications magazine)
Increasing demands are being placed on spectrum access, both domestic and abroad, as a result of current demands for global mobility, electromagnetic spectrum requirements of both outdated and future defense systems, and loss of military access to certain frequency bands due to spectrum legislation. Consequently, the DoD should identify shared spectrum access opportunities and explore dynamic spectrum access technologies to help meet the growing spectrum requirements of the military. This article discusses a few cases of current and future shared spectrum access environments to highlight the circumstances for spectrum sharing and utilization of military and commercial frequency bands.